Who feeds the cities?: a comparison of urban, peri-urban and rural food flows in Ghana - Drechsel, Pay (2014)
The present study quantified for the two major cities of Ghana, Accra and Kumasi, the contribution of peri-urban agriculture, rural agriculture and urban agriculture to urban food supply, and analysed how much of the nutrients needed in peri-urban areas could be recovered from urban waste recycling. While the majority of calorie rich food derives from rural areas, urban and peri-urban farms cover significant shares of certain, usually more perishable but vitamin rich commodities. With every harvest, the soils in the production areas export parts of their nutrients or soil fertility. Thus the “urban nutrient footprint” is significant and calls for options to close the rural-urban nutrient loop. Currently, between 70 and 80 % of the nitrogen and phosphorous consumed in Kumasi pollutes the urban environment, especially ground and surface water. Based on the available waste transport capacity in Kumasi, the entire nitrogen (N) and phosphorus (P) demand of urban farming could be covered, and 18 % of the N and 25 % of the P needs of peri-urban agriculture in a 40 km radius around Kumasi, if the already collected organic municipal waste and fecal sludge would be co-composted.